High-toughness anti-ablation hafnium tantalum carbon solid solution ceramic-based composite material and preparation method thereof
By doping silicon carbide whiskers in hafnium tantalum carbon solid solution ceramics and preparing SiCw-HfTaC2 composite materials in one-step using discharge plasma sintering method, the problem of insufficient fracture toughness and ablation resistance of hafnium tantalum carbon solid solution ceramics is solved, and high hardness is achieved , a combination of high toughness and excellent ablation resistance, meets the thermal protection material requirements of hypersonic aircraft.
Patent Information
- Application Number
- CN202411720050.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-02-14
AI Technical Summary
The existing hafnium tantalum carbon solid solution ceramic materials have low fracture toughness and poor ablation resistance, which cannot meet the mechanical performance requirements of thermal protection materials for hypersonic aircraft.
SiCw-HfTaC2 composite material is prepared in one step by doping silicon carbide whiskers in hafnium tantalum carbon solid solution ceramics to improve its fracture toughness and ablation resistance.
It significantly improves the hardness, fracture toughness and ablation resistance of hafnium tantalum carbon solid solution ceramics, meets the requirements of thermal protection materials for hypersonic aircraft, and simplifies the preparation process and reduces costs.
Smart Images

Figure CN119430975A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of composite materials, and further relates to a hafnium tantalum carbon solid solution ceramic-based composite technology, specifically a high-toughness and ablation-resistant hafnium tantalum carbon solid solution ceramic-based composite material and a preparation method thereof, which can be used for thermal structural protection materials such as nose cones and leading edges of hypersonic aircraft. Background Art
[0002] Long-range hypersonic aircraft are a technology that countries around the world are competing to research and develop. When a hypersonic aircraft is flying at high speed, its front end such as the nose cone and the leading edge of the wing will be subjected to rapid aerodynamic heating and high-speed airflow scouring. When the flight speed is greater than Mach 15, the temperature of the leading edge of the aircraft, the leading edge of the wing / rudder and other parts will exceed 3000°C, and ablation failure is very likely to occur. Ultra-high temperature hafnium tantalum carbon solid solution ceramics have great potential due to their high melting point (up to 4000°C), high hardness, and high strength. They can be used in thermal structural protection materials such as the nose cone and the leading edge of the wing of hypersonic aircraft. However, there are two key problems with hafnium tantalum carbon solid solution ceramics that need to be solved urgently. The first is that the fracture toughness of hafnium tantalum carbon solid solution ceramic materials is low, and it is easy to crack and fail as a coating; the second problem is that the Ta in the Hf-Ta-O oxide film generated by the oxidation of hafnium tantalum carbon solid solution ceramics during ultra-high temperature ablation is in gaseous form (Ta 1-x O x ) High temperature loss, resulting in a loose and porous structure Hf6Ta2O 17 The skeleton cannot continuously prevent the diffusion of oxygen.
[0003] In response to the first question, the existing literature "Consolidation and characterization of highly dense single-phase Ta-Hf-C solid solution ceramics" prepared hafnium-tantalum-carbon solid solution ceramics with different hafnium-tantalum ratios by hot pressing sintering, and the fracture toughness values of all component ceramics were only 2 to 3 MPa·m 1 / 2 The article "Harmonized toughening and strengthening in pressurelessly reactive-sintered Ta 0.8 Hf 0.2 C-SiC composite" by introducing SiC particles to prepare Ta 0.8 Hf 0.2 C-SiC composite material, but the maximum fracture toughness value of this composite material is only 4.5MPa·m 1 / 2. Therefore, the fracture toughness of hafnium tantalum carbon ceramics obtained by the researchers through the above-mentioned solid solution, multi-component regulation and introduction of SiC particles is still low and cannot meet the mechanical property requirements of thermal protection material components of hypersonic aircraft. In response to the second problem, the patent named "A reinforced ultra-high density ultra-high temperature ablation resistant coating and its preparation method" proposes introducing WC into the hafnium tantalum carbon solid solution ceramic coating by spraying, hoping that WO3 generated by oxidation of WC during ablation will fill the pores. However, it is well known that WO3 has a lower melting point than Ta2O5 and is more volatile, so the coating's ablation resistance is still poor.
[0004] It can be seen that the main problems existing in the prior art include the following: 1) The fracture toughness of hafnium tantalum carbon solid solution ceramics obtained by solid solution, multi-component regulation and introduction of sintering aid particles is still relatively low and the preparation process is complicated, which cannot meet the mechanical property requirements of thermal protection materials; 2) The Hf-Ta-O ablation layer generated by ablation and oxidation of hafnium tantalum carbon solid solution ceramics has insufficient temperature and oxygen resistance, and exhibits poor ultra-high temperature ablation resistance. As a thermal protection coating material for the surface of hypersonic aircraft, it is difficult to serve reliably for a long time; 3) Currently, two-step sintering method and hot pressing sintering method can be used to prepare whisker-toughened ceramic materials, but their preparation cost is high and time-consuming. Summary of the invention
[0005] The purpose of the present invention is to address the deficiencies of the above-mentioned prior art and propose a high-toughness and ablation-resistant hafnium-tantalum-carbon solid solution ceramic-based composite material and its preparation method, so as to solve the problems of low fracture toughness and poor ablation resistance of the prior art hafnium-tantalum-carbon solid solution ceramics. By doping hafnium-tantalum-carbon solid solution ceramics with silicon carbide whiskers, a SiC whisker-distributed uniformly distributed composite material is prepared. w -HfTaC2 composite material, in order to improve the fracture toughness of hafnium tantalum carbon solid solution ceramics and the high temperature thermal stability of their oxidation products, in order to simultaneously improve the cracking resistance and ablation resistance of hafnium tantalum carbon solid solution ceramics. The present invention can effectively improve the intrinsic brittleness of hafnium tantalum carbon solid solution ceramics, improve their fracture toughness and ablation resistance, and overcome the problem of easy fragmentation of ceramics and surface oxide layers during ablation.
[0006] In order to achieve the above-mentioned purpose, the present invention proposes a high-toughness and ablation-resistant hafnium-tantalum-carbon solid solution ceramic matrix composite material, which is a hafnium-tantalum-carbon solid solution ceramic SiC toughened by silicon carbide whiskers. w -HfTaC2 composite material, in which silicon carbide whiskers are uniformly distributed in the material; the above-mentioned SiC w -HfTaC2 composite material is prepared by fully mixing silicon carbide whiskers, hafnium carbide and tantalum carbide through spark plasma sintering and is obtained using a one-step sintering process.
[0007] Furthermore, the above SiC w-HfTaC2 composite material has a relative density greater than 93.30%, a Vickers hardness of 20.62-24.87 GPa, and a fracture toughness of 4.73-5.33 MPa·m 1 / 2 The mass ablation rate after ablation is between 0.73 and 0.44 mg / s -1 , the line ablation rate is between -4.72 and -2.17 μm / s -1 .
[0008] At the same time, a preparation method of a high-toughness and ablation-resistant hafnium-tantalum-carbon solid solution ceramic-based composite material is proposed, comprising the following steps:
[0009] (1) mixing hafnium carbide and tantalum carbide powders in a stoichiometric ratio of 1:1, adding anhydrous ethanol and placing in a ball milling jar, and then placing together with zirconium oxide medium balls in a planetary ball mill for mixed ball milling; placing the ball-milled slurry in a beaker, rotary evaporating the slurry through a rotary evaporator, drying the slurry, and finally grinding and sieving to obtain a mixed powder of hafnium carbide and tantalum carbide;
[0010] (2) placing silicon carbide whiskers in a beaker containing anhydrous ethanol for ultrasonic dispersion, and then adding a mixed powder of hafnium carbide and tantalum carbide, wherein the volume percentage of the mixed powder of hafnium carbide and tantalum carbide is 60 to 90 vol.%, and the volume percentage of silicon carbide whiskers is 10 to 40 vol.%; then performing uniform mixing, evaporating and drying operations on a rotary evaporator to obtain a mixed powder of silicon carbide whiskers, hafnium carbide and tantalum carbide;
[0011] (3) Using spark plasma hot pressing sintering, setting the sintering procedure steps, placing the mixed powder prepared in the above step (2) in a graphite mold for high-temperature sintering, and obtaining SiC w -HfTaC2 composite material.
[0012] Compared with the prior art, the present invention has the following advantages:
[0013] First, since the present invention uses silicon carbide whiskers doped with hafnium tantalum carbon solid solution ceramics, the hardness of the obtained composite material is increased from 20.32GPa to 24.87GPa, and the fracture toughness is increased from 2.67MPa·m 1 / 2 Increased to 5.33MPa·m 1 / 2 At the same time, the material's ablation resistance has also been significantly improved, with the mass ablation rate and line ablation rate of the hafnium tantalum carbon solid solution ceramic being 0.68 mg / s. -1 、-5.07μm / s -1 Reduced to 30 vol% SiC w -0.44mg / s for HfTaC2 composite -1 、-2.17μm / s -1The hardness and fracture toughness of the composite material obtained by the present invention are higher than the experimental values in other literatures, and the ablation performance is also better than the existing materials.
[0014] Second, since the present invention adopts the spark plasma hot pressing sintering method, the solid solution of hafnium carbide and tantalum carbide, and the integrated preparation of whiskers and solid solution ceramic composites are simultaneously achieved through a one-step sintering process; this process has the advantages of improving preparation efficiency and reducing costs.
[0015] Third, the present invention adopts spark plasma hot pressing sintering equipment, and reduces the agglomeration of silicon carbide whiskers through ultrasonic dispersion and rotary evaporation, so that the whiskers are evenly dispersed and the toughening effect of the whiskers is fully exerted; the impurities introduced by the use of traditional dispersants are reduced in the preparation process, and based on the pinning effect of the second phase, the adverse effects of grain growth on the mechanical properties of ceramics are suppressed.
[0016] The present invention adopts SiC prepared by one-step sintering of silicon carbide whisker doped with hafnium tantalum carbon solid solution ceramic w -HfTaC2 composite material, which has achieved a combination of high hardness, high toughness and excellent ablation resistance, breaking the tradition that the material preparation method can only obtain single function optimization; and providing a high-efficiency and low-cost SiC w -HfTaC2 composite material preparation method, can realize the preparation of high-toughness and ablation-resistant hafnium tantalum carbon solid solution ceramic-based composite materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 The SiC obtained in Example 4 of the present invention w -SEM surface morphology of HfTaC2 composite material;
[0018] Figure 2 The SiC obtained in Example 5 of the present invention w -XRD pattern of HfTaC2 composite material;
[0019] Figure 3 The SiC obtained in Examples 3 to 6 of the present invention w -Comparison of fracture toughness and hardness of HfTaC2 composite material and hafnium tantalum carbon solid solution ceramic;
[0020] Figure 4 The SiC obtained in Examples 3 to 6 of the present invention w -Comparison of the anti-ablation performance of HfTaC2 composite materials and hafnium tantalum carbon solid solution ceramics;
[0021] Figure 5 The SiC obtained in Examples 3 to 6 of the present invention w -Surface SEM images and EDS scanning results of HfTaC2 composite materials and hafnium tantalum carbon solid solution ceramics after ablation. DETAILED DESCRIPTION
[0022] The present invention will be further described below in conjunction with the accompanying drawings.
[0023] Embodiment 1: Refer to the attached Figure 1 The present invention proposes a high-toughness and ablation-resistant hafnium-tantalum-carbon solid solution ceramic matrix composite material, specifically a hafnium-tantalum-carbon solid solution ceramic SiC toughened by silicon carbide whiskers. w -HfTaC2 composite material, wherein silicon carbide whiskers are uniformly distributed in the material; the SiC w -HfTaC2 composite material is prepared by mixing silicon carbide whiskers, hafnium carbide and tantalum carbide, and then sintering by spark plasma, and is obtained by a one-step sintering process. w -HfTaC2 composite material has a relative density greater than 93.30%, a Vickers hardness of 20.62-24.87 GPa, and a fracture toughness of 4.73-5.33 MPa·m 1 / 2 The mass ablation rate after ablation is between 0.73 and 0.44 mg / s -1 , the line ablation rate is between -4.72 and -2.17 μm / s -1 .
[0024] The present invention proposes a viewpoint based on fiber-tough ceramic matrix composite materials, adopts silicon carbide whisker one-dimensional material as toughening phase, and prepares silicon carbide whisker doped hafnium tantalum carbon solid solution ceramic matrix composite materials (SiC w -HfTaC2), which can improve the fracture toughness of hafnium-tantalum-carbon solid solution ceramics; at the same time, it is hoped that SiC will be ablated and oxidized at high temperature to generate SiO2 glass with suitable viscosity, which can heal the loose and porous Hf6Ta2O 17 skeleton, forming a dense oxygen barrier layer of Hf-Ta-Si-O with high thermal stability.
[0025] Embodiment 2: Refer to the attached Figure 1 The method for preparing the high-toughness and ablation-resistant hafnium tantalum carbon solid solution ceramic-based composite material proposed in the present invention specifically comprises the following steps:
[0026] Step 1. Mix hafnium carbide and tantalum carbide powders in a stoichiometric ratio of 1:1, add anhydrous ethanol and place in a ball mill, and then place together with zirconium oxide medium balls in a planetary ball mill for mixed ball milling; then place the ball-milled slurry in a beaker, rotary evaporate the slurry through a rotary evaporator, dry it, and finally grind and sieve to obtain a mixed powder of hafnium carbide-tantalum carbide.
[0027] The hafnium carbide and tantalum carbide powders in this step of the present embodiment have a particle size of 1.0 to 3.0 μm. When the slurry is rotary evaporated and dried by a rotary evaporator, the rotation speed is set to 600 to 800 r / min.
[0028] Step 2. Place the silicon carbide whisker in a beaker containing anhydrous ethanol for ultrasonic dispersion, then add a mixed powder of hafnium carbide and tantalum carbide, wherein the volume percentage of the mixed powder of hafnium carbide and tantalum carbide is 60-90 vol.%, and the volume percentage of the silicon carbide whisker is 10-40 vol.%; then perform uniform mixing, evaporate to dryness, and dry on a rotary evaporator to obtain a mixed powder of silicon carbide whiskers, hafnium carbide and tantalum carbide.
[0029] In this embodiment, silicon carbide whiskers are placed in a beaker containing anhydrous ethanol for ultrasonic dispersion, wherein the diameter of the silicon carbide whiskers is 0.1-0.6 μm and the length is 10-50 μm. The ultrasonic dispersion is performed for a time of 10-30 min and a power of 80-100 W; the mixing, evaporation and drying operations are performed on a rotary evaporator, and the rotation speed is set to 100-300 r / min and the drying temperature is set to 100-300°C.
[0030] Step 3. Use spark plasma hot pressing sintering, set the sintering program steps, place the mixed powder prepared in step (2) above in a graphite mold for high temperature sintering, and obtain SiC w -HfTaC2 composite material.
[0031] In the above-mentioned high-temperature sintering process in this embodiment, the set temperature is 1800-2000°C, the insulation time is 10-30min, the pressure is 30-45MPa, and the heating rate is 50-100°C / min; and after the insulation program is completed, it is cooled at a rate of 50-100°C / min.
[0032] Embodiment 3: The overall implementation steps of this embodiment are the same as those of Embodiment 2. Now, given the first specific parameter setting, the implementation process of the present invention is further described in the form of a specific example:
[0033] Step A: The molar ratio of the original powders of hafnium carbide and tantalum carbide is 1:1, and the mixed powder of hafnium carbide and tantalum carbide and silicon carbide whiskers with a volume percentage of 90:10 are used as raw materials. First, the mixed powder of hafnium carbide and tantalum carbide is placed in a drum ball mill and mixed with anhydrous ethanol for ball milling. During the ball milling process, the ball-to-material ratio is 5:1, the rotation speed is 300r / min, and the time is 6h to obtain a mixed slurry of hafnium carbide and tantalum carbide. Then the mixed slurry is placed in a beaker, and rotary evaporation and drying are performed by a rotary evaporator to obtain a uniform mixed powder of hafnium carbide and tantalum carbide, wherein the rotation speed is 600r / min;
[0034] Step B: placing silicon carbide whiskers in a beaker containing anhydrous ethanol for 20 minutes and ultrasonic dispersion at a power of 100 W, then adding the powder obtained in step A, mixing evenly and evaporating on a rotary evaporator, and further drying to obtain a uniform mixed powder of silicon carbide whiskers, hafnium carbide and tantalum carbide, the rotation speed is 100 r / min, and the rotary evaporation temperature is 200° C.;
[0035] Step C: The ceramic mixed powder obtained in step B is loaded into a graphite mold, placed in a discharge plasma hot pressing sintering furnace, the heating rate is 100°C / min, and the temperature is kept at 1800°C and 45MPa for 30 minutes. After the insulation program is completed, the temperature is reduced at a rate of 100°C / min, and the temperature is reduced with the furnace after 800°C to obtain a hafnium tantalum carbon solid solution ceramic material toughened by silicon carbide whiskers.
[0036] The whisker-toughened hafnium-tantalum-carbon solid solution ceramic prepared in this embodiment has a relative density of 93.3%, a hardness of 20.32 GPa, and a fracture toughness of 4.73 MPa·m 1 / 2 , mass ablation rate is 0.73mg / s -1 , linear ablation rate is -4.72μm / s -1 The density of the sample was tested by the Archimedes drainage method, the hardness and modulus were tested by the nanoindentation method, the fracture toughness was tested by the indentation method, and the ablation resistance was tested by the oxyacetylene ablation test, which is the same as in the following Examples 4 to 6.
[0037] Embodiment 4: The overall implementation steps of this embodiment are the same as those of Embodiment 2. Now, a second specific parameter setting is given to further describe the implementation process of the present invention in the form of a specific example:
[0038] Step 1). The molar ratio of the original powders of hafnium carbide and tantalum carbide is 1:1, and the hafnium tantalum carbon mixed powder and silicon carbide whiskers with a volume percentage of 80:20 are used as raw materials. First, the mixed powder of hafnium carbide and tantalum carbide is placed in a drum ball mill and mixed with anhydrous ethanol for ball milling. During the ball milling process, the ball-to-material ratio is 5:1, the rotation speed is 300r / min, and the time is 6h to obtain a mixed slurry of hafnium carbide and tantalum carbide. Then the mixed slurry is placed in a beaker, and rotary evaporation and drying are performed by a rotary evaporator to obtain a uniform mixed powder of hafnium carbide and tantalum carbide, wherein the rotation speed is 700r / min;
[0039] Step 2). The silicon carbide whisker is placed in a beaker containing anhydrous ethanol for 20 minutes and ultrasonic dispersion at a power of 100 W, and then the powder obtained in step 1) is added, mixed evenly on a rotary evaporator, evaporated to dryness, and further dried to obtain a uniform mixed powder of silicon carbide whiskers, hafnium carbide and tantalum carbide, the rotation speed is 100r / min, and the rotary evaporation temperature is 200°C;
[0040] Step 3). The ceramic mixed powder obtained in step 2) is loaded into a graphite mold and placed in a discharge plasma hot pressing sintering furnace. The heating rate is 100°C / min, and the temperature is kept at 1900°C and 40MPa for 20min. After the insulation program is completed, the temperature is cooled at a rate of 80°C / min. After 800°C, the temperature is cooled with the furnace to obtain SiC w -HfTaC2 composite material.
[0041] The whisker-toughened hafnium-tantalum-carbon solid solution ceramic prepared in this embodiment has a relative density of 94.2%, a hardness of 23.01 GPa, and a fracture toughness of 5.05 MPa·m 1 / 2 , mass ablation rate is 0.75mg / s -1 , linear ablation rate is -2.87μm / s -1 .
[0042] Figure 1 The SiC obtained in Example 4 w -SEM surface morphology of HfTaC2 composite material. Figure 1 It can be seen that the whiskers are distributed evenly, indicating that the ultrasonic dispersion and rotary evaporator have a good dispersion effect on the whiskers, the plasma sintering process used is appropriate, and a large number of whiskers in the composite material maintain intact morphology to achieve better toughening effect.
[0043] Embodiment 5: The overall implementation steps of this embodiment are the same as those of Embodiment 2. Now, a third specific parameter setting is given to further describe the implementation process of the present invention in the form of a specific example:
[0044] Step 1. The molar ratio of the original powders of hafnium carbide and tantalum carbide is 1:1, and the raw materials are hafnium tantalum carbon powder and silicon carbide whiskers with a volume percentage of 70:30. First, add the mixed powders of hafnium carbide and tantalum carbide into a drum ball mill and mix with anhydrous ethanol for ball milling. During the ball milling process, the ball-to-material ratio is 5:1, the rotation speed is 300r / min, and the time is 6h to obtain a mixed slurry of hafnium carbide and tantalum carbide. Then, the mixed slurry is placed in a beaker, and a rotary evaporator is used to perform rotary evaporation and drying to obtain a uniform mixed powder of hafnium carbide and tantalum carbide. Among them, the rotation speed is 800r / min, and the rotary evaporation temperature is 200°C;
[0045] Step 2. Place the silicon carbide whisker in a beaker containing anhydrous ethanol for 20 minutes and ultrasonic dispersion at a power of 100 W, then add the powder obtained in step 1, mix evenly on a rotary evaporator, evaporate to dryness, and further dry to obtain a uniform mixed powder of silicon carbide whiskers, hafnium carbide and tantalum carbide, the rotation speed is 100 r / min, and the rotary evaporation temperature is 200 ° C;
[0046] Step 3. The ceramic mixed powder obtained in step 2 is loaded into a graphite mold and placed in a spark plasma hot pressing sintering furnace. The heating rate is 80°C / min, and the temperature is kept at 1800°C and 40MPa for 10 minutes. After the insulation program is completed, the temperature is cooled at a rate of 80°C / min. After 800°C, the temperature is cooled with the furnace to obtain SiC w -HfTaC2 composite material.
[0047] The SiC prepared in this example w -HfTaC2 composite material has a relative density of 95.7%, a hardness of 23.01GPa, and a fracture toughness of 5.33MPa·m 1 / 2 , mass ablation rate is 0.44mg / s -1 , linear ablation rate is -2.17μm / s -1 .
[0048] Figure 2 The SiC obtained in Example 5 w -XRD pattern of HfTaC2 composite material. Figure 2 It can be seen that the phases of the composite material are hafnium tantalum carbon solid solution ceramic and silicon carbide phase, and the diffraction peaks are relatively obvious. The introduction of silicon carbide in the preparation process of the composite material has no effect on the formation of solid solution of hafnium tantalum carbon powder.
[0049] Embodiment 6: The overall implementation steps of this embodiment are the same as those of Embodiment 2. Now, a third specific parameter setting is given to further describe the implementation process of the present invention in the form of a specific example:
[0050] Step a. The molar ratio of the original powders of hafnium carbide and tantalum carbide is 1:1, and hafnium tantalum carbon powder and silicon carbide whiskers with a volume percentage of 60:40 are used as raw materials. First, the mixed powder of hafnium carbide and tantalum carbide is placed in a drum ball mill and mixed with anhydrous ethanol for ball milling. During the ball milling process, the ball-to-material ratio is 5:1, the rotation speed is 300r / min, and the time is 6h to obtain a mixed slurry of hafnium carbide and tantalum carbide. Then the mixed slurry is rotary evaporated and dried through a rotary evaporator to obtain a uniform mixed powder of hafnium carbide and tantalum carbide. Among them, the rotation speed is 800r / min, and the rotary evaporation temperature is 200°C;
[0051] Step b. placing the silicon carbide whisker in a beaker containing anhydrous ethanol for 20 min at a power of 100 W for ultrasonic dispersion, then adding the powder obtained in step a, mixing evenly on a rotary evaporator, evaporating to dryness, and further drying to obtain a uniform mixed powder of silicon carbide whiskers, hafnium carbide and tantalum carbide, the rotation speed is 100 r / min, and the rotary evaporation temperature is 200 ° C;
[0052] Step c. The ceramic mixed powder obtained in step b is loaded into a graphite mold and placed in a spark plasma hot pressing sintering furnace. The heating rate is 100°C / min, and the temperature is kept at 1850°C and 40MPa for 15min. After the insulation program is completed, the temperature is cooled at a rate of 100°C / min. After 800°C, the temperature is cooled with the furnace to obtain SiC w -HfTaC2 composite material.
[0053] The SiC prepared in this example w -HfTaC2 composite material has a relative density of 94.9%, a hardness of 21.17GPa, and a fracture toughness of 4.76MPa·m 1 / 2 , mass ablation rate is 0.55mg / s -1 , linear ablation rate is -3.62μm / s -1 .
[0054] Parts of the present invention that are not described in detail belong to common knowledge among those skilled in the art.
[0055] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Obviously, for professionals in this field, after understanding the content and principles of the present invention, they may make various modifications and changes in form and details without departing from the principles and structures of the present invention. However, these modifications and changes based on the ideas of the present invention are still within the scope of protection of the claims of the present invention.
Claims
1. A high-toughness, ablation-resistant hafnium-tantalum-carbon solid solution ceramic matrix composite material, characterized in that: It is a hafnium-tantalum-carbon solid solution ceramic SiC toughened by silicon carbide whiskers w -HfTaC2 composite material, wherein silicon carbide whiskers are uniformly distributed in the material; the SiC w -HfTaC2 composite material is prepared by fully mixing silicon carbide whiskers, hafnium carbide and tantalum carbide through spark plasma sintering and is obtained using a one-step sintering process.
2. The composite material according to claim 1, characterized in that: The SiC w -HfTaC2 composite material has a relative density greater than 93.30%, a Vickers hardness of 20.62-24.87 GPa, and a fracture toughness of 4.73-5.33 MPa·m 1 / 2 The mass ablation rate after ablation is between 0.73 and 0.44 mg / s -1 , the line ablation rate is between -4.72 and -2.17 μm / s -1 .
3. A method for preparing a high-toughness, ablation-resistant hafnium-tantalum-carbon solid solution ceramic-based composite material, characterized in that: The steps include: (1) mixing hafnium carbide and tantalum carbide powders in a stoichiometric ratio of 1:1, adding anhydrous ethanol and placing in a ball milling jar, and then placing together with zirconium oxide medium balls in a planetary ball mill for mixed ball milling; placing the ball-milled slurry in a beaker, rotary evaporating the slurry through a rotary evaporator, drying the slurry, and finally grinding and sieving to obtain a mixed powder of hafnium carbide and tantalum carbide; (2) placing silicon carbide whiskers in a beaker containing anhydrous ethanol for ultrasonic dispersion, and then adding a mixed powder of hafnium carbide and tantalum carbide, wherein the volume percentage of the mixed powder of hafnium carbide and tantalum carbide is 60 to 90 vol.%, and the volume percentage of silicon carbide whiskers is 10 to 40 vol.%; then performing uniform mixing, evaporating and drying operations on a rotary evaporator to obtain a mixed powder of silicon carbide whiskers, hafnium carbide and tantalum carbide; (3) Using spark plasma hot pressing sintering, setting the sintering procedure steps, placing the mixed powder prepared in the above step (2) in a graphite mold for high-temperature sintering, and obtaining SiC w -HfTaC2 composite material.
4. The method according to claim 3, characterized in that: The hafnium carbide and tantalum carbide powders in step (1) both have a particle size of 1.0 to 3.0 μm.
5. The method according to claim 3, characterized in that: In step (1), when the slurry is rotary evaporated and dried by a rotary evaporator, the rotation speed is set to 600-800 r / min.
6. The method according to claim 3, characterized in that: In step (2), the silicon carbide whiskers are placed in a beaker containing anhydrous ethanol for ultrasonic dispersion, wherein the silicon carbide whiskers have a diameter of 0.1 to 0.6 μm and a length of 10 to 50 μm.
7. The method according to claim 3, characterized in that: In step (2), the ultrasonic dispersion is performed with a setting time of 10 to 30 minutes and a power of 80 to 100 W; the mixing, evaporation and drying operations are performed on a rotary evaporator with a setting rotation speed of 100 to 300 r / min and a drying temperature of 100 to 300° C.
8. The method according to claim 3, characterized in that: The high temperature sintering in step (3) is set at a temperature of 1800-2000°C, a holding time of 10-30 min, a pressure of 30-45 MPa, and a heating rate of 50-100°C / min; and after the holding program is completed, the temperature is cooled at a rate of 50-100°C / min.